Perceived quality of care for severe acute malnutrition management among caregivers of under-five children with severe acute malnutrition in Addis Ababa, Ethiopia, 2022: a mixed-method study - Adema, Bulcha Guye; Atnafu, Niguse Tadele; Ashagre, Feven Mulugeta (Frontiers in Public Health, 2023)
Factors at the institutional, provider and client levels all have an impact on care quality. In low and middle-income countries, poor quality SAM management at health institutions is a major contributor to child morbidity and mortality. The aim of this study is to determine the perceived quality of care of SAM management, among under-five children in the selected public health facilities in Addis Ababa city administration, Ethiopia in 2022. Methods: An institution-based convergent mixed study design was implemented. The data collection was conducted from February 15 to May 20, 2022, through structured questionnaires and in-depth interviews. Open data kit (ODK) version 1.0 was used for data collection and exported to Excel, then imported to STATA version 16 for analysis. A total of 181 caregivers were recruited consecutively for quantitative analysis. The data was analyzed by using a logistic regression model. A total of 15 healthcare providers were recruited and thematic analysis was used with the assistance of Atlas ti. version 9.1. Result: Overall, the perceived quality of care of SAM management was 55.80% (CI: 48.5-63.10). Urban residence (AOR=0.32, 95% CI: 0.16-0.66), Parental education level (college and above) (AOR=4.42, 95% CI: 1.41-13.86), parents government employee (AOR= 2.72, 95% CI: 1.05-7.05), readmitted to the hospital (AOR= 0.47, 95% CI: 0.23-0.94), length of hospital stays greater than seven days (AOR=2.1, 95% CI: 1.01-4.27) were found to be significantly associated factors with perceived low-level quality care SAM management. A qualitative study found that lack of support and attention from higher levels of institutions (AAHB and MOH), lack of supplements, lack of separate units, and lack of laboratory requests were among the factors that mask quality care in SAM management. Conclusion and recommendations: Perception was shown to be low in the current investigation. The responsible authority should take the necessary steps to improve the quality of SAM management.